Reconstructing Anti- Strategic Lawsuits Against Public Participation Regulation: A Legal-Political Response to 'Rubber Articles' and Democratic Regression in Indonesia's Criminal Justice System - Nabela, Nadia; MPB, Andi Srikandi; Basuki, Teguh (Faculty of Law, Universitas Pattimura, 2026)
Introduction: This study analyzes the systemic threat of Strategic Lawsuits Against Public Participation (SLAPPs) to Indonesian democracy, particularly how 'rubber articles' within the criminal law are weaponized to silence dissent. Purposes of the Research: The research evaluates the legal politics perpetuating SLAPPs and proposes the urgent establishment of comprehensive, cross-sectoral Anti-SLAPP regulations. Employing qualitative doctrinal legal research with statute, conceptual, and comparative approaches. Methods of the Research: The method used in this study is qualitative doctrinal legal research to examine criminal law practices. The research comprehensively integrates three main approaches, namely a statute approach, a conceptual approach, and a comparative approach. Primary and secondary legal materials were collected through structured documentary study and analyzed prescriptively. Findings of the Research: it finds that multi-interpretable norms in the Electronic Information and Transactions Law and Criminal Code, coupled with a lack of early dismissal mechanisms, create a chilling effect and undermine constitutional rights. This research recommends legal reconstruction through the adoption of Anti-SLAPP regulations, including constitutional threshold tests and cost-shifting rules, to protect democratic integrity and restore the rule of law. Keywords: Anti-SLAPP; Legal Politics; Rubber Articles; Criminalization; Constitutionalism.